2021
DOI: 10.1186/s12992-021-00770-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparing COVID-19 physical distancing policies: results from a physical distancing intensity coding framework for Botswana, India, Jamaica, Mozambique, Namibia, Ukraine, and the United States

Abstract: Background Understanding the differences in timing and composition of physical distancing policies is important to evaluate the early global response to COVID-19. A physical distancing intensity monitoring framework comprising 16 domains was recently published to compare physical distancing approaches across 12 U.S. States. We applied this framework to a diverse set of low and middle-income countries (LMICs) (Botswana, India, Jamaica, Mozambique, Namibia, and Ukraine) to test the appropriatenes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Such hypotheses are also made for populated countries such as Brazil, China, India, and the United States 53 as well as for low- and middle-income countries (Botswana, India, Jamaica, Mozambique, Namibia, and Ukraine). 54 This work extends the study by Lane et al 54 by exploring analyses of up to 906 (they used 100) days from the onset of COVID-19.…”
Section: Discussionmentioning
confidence: 56%
“…Such hypotheses are also made for populated countries such as Brazil, China, India, and the United States 53 as well as for low- and middle-income countries (Botswana, India, Jamaica, Mozambique, Namibia, and Ukraine). 54 This work extends the study by Lane et al 54 by exploring analyses of up to 906 (they used 100) days from the onset of COVID-19.…”
Section: Discussionmentioning
confidence: 56%
“…Data were collected over the period of March and October 2020. By March 2020, since the World Health Organization (WHO) had declared COVID-19 a “Public Health Emergency of International Concern” on 30 January 2020 and a “pandemic” (p. 2) on 11 March 2020 ( Lane et al, 2021 , p. 2), all the countries considered in the current study already had introduced some policies and containment measures during (or before) the month of March 2020; details and timelines can be found at United Nations [UN] (2022) for Angolo, Nchanji and Lutomia (2021) for Eswatini, Lesotho, and Kenya, Lane et al (2021) for Mozambique and Namibia, and Haider et al (2020) for South Africa, Uganda and Zambia. As all countries were aware of the global public health emergency status and had implemented some level of response measures to address the pandemic’s impact by the time of data collection, although we cannot measure how the COVID-19 pandemic restrictions may have impacted the adolescents’ responses, the adolescents’ experiences were captured in all nine counties under the shared knowledge and awareness of COVID-19’s severity and implications.…”
Section: Methodsmentioning
confidence: 99%
“…Despite this, we had a good buy in from the community due to our extensive community engagement conducted before and during the study, which also resulted in higher participation rates in general than previously observed in other sub-Saharan African settings. Furthermore, the data was collected during periods of active transmission of SARS-CoV-2 in the community, including certain times when certain restrictive measures were in place, such as the closure of schools and parks, limitations on the number of employees at the workplace and passengers on public transportation, social distancing, and other measures [23]. This context likely caused some disruption, given the contingency scenario at the time, and may have influenced the characteristics of social contact patterns due to the ongoing pandemic.…”
Section: Acknowledgementsmentioning
confidence: 99%